Extracellular signal-regulated kinases 1/2 as regulators of cardiac hypertrophy - Mutlak, Michael; Kehat, Izhak (Frontiers in Pharmacology, 2015)
Cardiac hypertrophy results from increased mechanical load on the heart and through the actions of local and systemic neuro-humoral factors, cytokines and growth factors. These mechanical and neuroendocrine effectors act through stretch, G protein-coupled receptors and tyrosine kinases to induce the activation of a myriad of intracellular signaling pathways including the extracellular signal-regulated kinases 1/2 (ERK1/2). Since most stimuli that provoke myocardial hypertrophy also elicit an acute phosphorylation of the threonine-glutamate-tyrosine (TEY) motif within the activation loops of ERK1 and ERK2 kinases, resulting in their activation, ERKs have long been considered promotors of cardiac hypertrophy. Several mouse models were generated in order to directly understand the causal role of ERK1/2 activation in the heart. These models include direct manipulation of ERK1/2 such as overexpression, mutagenesis or knockout models, manipulations of upstream kinases such as MEK1 and manipulations of the phosphatases that depohosphorylate ERK1/2 such as DUSP6. The emerging understanding from these studies, as will be discussed here, is more complex than originally considered. While there is little doubt that ERK1/2 activation or the lack of it modulates the hypertrophic process or the type of hypertrophy that develops, it appears that not all ERK1/2 activation events are the same. While much has been learned, some questions remain regarding the exact role of ERK1/2 in the heart, the upstream events that result in ERK1/2 activation and the downstream effector in hypertrophy.